Dinâmica térmica em cutias (Dasyprocta leporina Linnaeus, 1758) e preás (Galea spixii Wagler, 1831) em ambiente semiárido neotropical - Queiroz, João Paulo Araújo Fernandes de (2016)
Because the thermoregulation of red-rumped agouti (Dasyprocta leporina Linneus, 1758) and Spix’s yellow-toothed cavy (Galea spixii Wagler, 1831) facing a semiarid environment remain unknown, this study aimed to determine the evaporative heat loss and heat exchanges by radiation and convection. Twenty red-rumped agoutis and twenty-eight Spix’s yellow-toothed cavies were used in different experiments. Red-rumped agoutis were subjected to eight samplings days, and the data collection was performed in five times (7h00, 9h00, 11h00, 14h00 and 16h00). Each Spix’s yellow-toothed cavy was subjected to three sampling days, with data collection performed at hourly intervals, from 6h00 to 13h00. The thermal environment was monitored in each data collection. The body surface temperature was measured by infrared thermography. The body regions considered in the thermograms of red-rumped agoutis were nose, eyes, pinna, body, fore and hindlimbs. In addition to those mentioned for agoutis, thermograms of Spix’s yellow-toothed cavies considered the vibrissae and periocular regions. Evaporative heat loss was determined by calorimetry. The pinna (13.10±1.17 W m-2) and hindlimbs (11.19±1.17 W m-2) of the agoutis were the main regions involved in heat loss by radiation, working as thermal windows. The radiation was higher in the periocular regions (45.23±0.81 W m-2), followed by the eyes surface (41.41±0.81 W m-2), pinna (31.56±0.80 W m-2) and vibrissae (27.03±0.80 W m-2). The periocular temperatures proved to be a valuable predictor of rectal temperature of the cavies, showing a correlation coefficient of 0.61. The convection in agoutis was more intense in the body and hindlimbs at all day times. In cavies, the convection was insignificant (0.54±0.56 W m-2). Evaporative heat loss in agoutis (52.53±1.64 W m-2) and cavies (143.69±1.37 W m-2) was more intense when the atmospheric temperature was higher. Thus, we observe that both non-evaporative and evaporative mechanisms are important for the maintenance of homeothermy in red-rumped agouti and Spix’s yellow-toothed cavy in a hot environment. These rodents use specialized body regions in the heat transfer, the thermal windows